(untitled) (Itinera, 2017)
The observatory TEMPO (Theatrical Enjoyment Measurement and Production Observation-Centre) was founded in January 2016 at the University of Milan, in the context of the European project “Senses: the Sensory Theatre – New Transnational Strategies for Theatre Audience Building”. It aims at developing new strategies to bring young people closer to theatre, through both the education of young spectators and the production of plays that can attract their interest. The Observatory aims therefore at giving back to theatre a political and social function that is essential for it.